If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 2x + -5 Reorder the terms: 15 + 3x = 2x + -5 Reorder the terms: 15 + 3x = -5 + 2x Solving 15 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x 15 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 1x = -5 + 0 15 + 1x = -5 Add '-15' to each side of the equation. 15 + -15 + 1x = -5 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = -5 + -15 1x = -5 + -15 Combine like terms: -5 + -15 = -20 1x = -20 Divide each side by '1'. x = -20 Simplifying x = -20
| 8-(6-7)=0 | | 8(x+4)=-64 | | 3y+2y=2y-5x | | X+m=no+rq | | 7x-32-9x=8 | | Y=3x^5+3x^3-60x | | -6-(6-6p)=0 | | 4(4-4x)+4=-2x+2-14x | | 5-9+x=65 | | -4=4(3-b) | | 6x+3(4x+2)=96 | | -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 | | 15x+3x-4=14whatisx | | 3x+5x+5=11+10x+6 | | 6(x+3)+7-x=4x(x+3) | | S-15=15.19 | | 8X-14=7X+9 | | 9(x-2)=72 | | 3(2x-5)+6=4x+7 | | 4(x-3)=x-5 | | 5d+15-2d-10=11 | | 256+5546=x | | 8+3x=-4x+57 | | 4x+3(4x-6)=110 | | -3+4x=4(x-7)+25 | | -6x+8y=-22 |